2005
DOI: 10.1016/j.bbrc.2005.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated GSK3β activity in colorectal cancer: Its association with tumor cell survival and proliferation

Abstract: GSK3β is a multifunctional serine/threonine kinase that regulates various cellular pathways, depending on its substrates for phosphorylation. It is evident that regulation of Wnt/β-catenin signaling is only one of its diverse functions. Since oncogenic transcription factors (e.g., c-Jun, c-Myc) and proto-oncoproteins (i.e., β-catenin, Gli proteins) are putative GSK3β substrates for phosphorylation-dependent inactivation, it is hypothesized that GSK3β interferes with cellular neoplastic transformation and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
269
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(299 citation statements)
references
References 23 publications
27
269
2
1
Order By: Relevance
“…More recent studies indicate a role for GSK3 in the control of neoplastic transformation and tumor development (reviewd in Miyashita et al, 2009b). Overexpression and activation of GSK3 was confirmed in various kinds of cancers such as colorectal, stomach, pancreatic, and liver cancers, as well as leukemia and GBM (Shakoori et al, 2005;Shakoori et al, 2007;Wang et al, 2008;Miyashita et al, 2009a;Mai et al, 2009). Previous studies have shown that inhibition of GSK3 suppresses cancer cell proliferation and induces apoptosis Ougolkov et al, 2007).…”
Section: Pathological Functionmentioning
confidence: 96%
“…More recent studies indicate a role for GSK3 in the control of neoplastic transformation and tumor development (reviewd in Miyashita et al, 2009b). Overexpression and activation of GSK3 was confirmed in various kinds of cancers such as colorectal, stomach, pancreatic, and liver cancers, as well as leukemia and GBM (Shakoori et al, 2005;Shakoori et al, 2007;Wang et al, 2008;Miyashita et al, 2009a;Mai et al, 2009). Previous studies have shown that inhibition of GSK3 suppresses cancer cell proliferation and induces apoptosis Ougolkov et al, 2007).…”
Section: Pathological Functionmentioning
confidence: 96%
“…Recent work in colorectal cancer, pancreatic cancer and hepatocellular carcinoma [2][3][4] demonstrates that glycogen synthase kinase-3β (GSK-3β) is involved in the process of tumorigenesis. Inhibition of the expression and activity of GSK-3β attenuates cell proliferation and causes apoptosis in colorectal and pancreatic cancer cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the expression and activity of GSK-3β attenuates cell proliferation and causes apoptosis in colorectal and pancreatic cancer cells [2,3]. In contrast, activation of GSK-3β by LY294002 sensitizes hepatoma cells to chemotherapy-induced apoptosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our unpublished data have also shown that the expression of phosphorylated GSK3 is significantly higher in the tumor tissue of EC than normal tissue. However, other studies indicate that GSK3b is overexpressed in many human malignancies that may offset the observed phospho-inactivation (Ougolkov et al 2006;Shakoori et al 2005). Future work should aim at determining the role of GSK3 in an in vivo setting, under the pressures of the host immune response, and during various stages of the disease since GSK3 activity, like many proteins, could shift drastically during disease progression.…”
Section: Gsk3b Affects Tumorigenesis Of Ec Via Regulating Cell Cyclementioning
confidence: 99%